2010
DOI: 10.1111/j.1468-3083.2010.03671.x
|View full text |Cite
|
Sign up to set email alerts
|

On the development of the European S3 guidelines on the systemic treatment of psoriasis vulgaris: structure and challenges

Abstract: The development of European evidence based guidelines requires a coordinated structure which can be achieved by the integration of an experienced group of methodologists. Nevertheless further improvements are imaginable and might be considered for an update or other European evidence based guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 9 publications
1
45
0
5
Order By: Relevance
“…10) and documented intolerance or contraindication of standard systemic treatments. Hungarian Guideline on Psoriasis Therapies is based on and synchronized with the European S3 Psoriasis Guideline in accordance with the financing protocol of the NHIF (13).…”
Section: Patient Enrollmentmentioning
confidence: 99%
“…10) and documented intolerance or contraindication of standard systemic treatments. Hungarian Guideline on Psoriasis Therapies is based on and synchronized with the European S3 Psoriasis Guideline in accordance with the financing protocol of the NHIF (13).…”
Section: Patient Enrollmentmentioning
confidence: 99%
“…Studies of ADA treatment in rats are limited. It was reported that the highest serum level of ADA could be achieved after of 5 days of subcutaneous administration [36]. In this study we administered ADA intraperitoneally 5 days before giving I/R and demonstrated that it was protective in I/R.…”
Section: Discussionmentioning
confidence: 49%
“…That is why it is more difficult to reveal the cause-effect relation [6][7][8]17]. It is also important that it is not always possible to track these phenomena through time, namely, efficacy [effect obtained in "ideal conditions" of randomized placebo-controlled trials (RCT)].…”
Section: General Adverse Phenomenamentioning
confidence: 99%
“…Areas of use of them are extremely versatile: endocrinology, oncology, rheumatology, oncohematology and hematology. The modern leaders in the group of BP are monoclonal antibodies to various receptors, enzymes and macroorganism's cells [6][7][8][9][10][11]:…”
mentioning
confidence: 99%